Epistemologi Filsafat Pancasila dalam Pembangunan Politik dan Hukum di Indonesia - Anselmus Leduq; Benediktus Hestu Cipto Handoyo (Jurnal USM Law Review)
This study aims to build a healthy political and legal life and democratization based on the elements and sources of truth of the epistemological values of Pancasila. This study needs to be studied because the development of political and legal life in Indonesia today is increasingly unstable in political dynamics. The law which is considered as the commander of the state, is now weakened in order to perpetuate or smooth the power of individuals or groups of people in politics, there is a lot of corruption, collusion, and nepotism (KKN). The increasingly complex political and legal dynamics are increasingly moving away from the values of Pancasila. The research method used is a qualitative descriptive method with a historical and philosophical approach. The results of the study show that the dynamics of politics and law in Indonesia are not running healthily and democratically because they are not built on the values of Pancasila as the basis of the State. Politics and law are now built on the ambition of group and individual power so there is a lot of corruption, collusion, and nepotism (KKN). The conclusion of this study is to try to uncover the ideas, sources, origins, and essence of knowledge from the values of Pancasila as the nation's ideology and apply them to the dynamics of political and legal life in Indonesia. These values are divinity, humanity, unity, democracy, human rights, justice, certainty, and the benefits of law.